2019
DOI: 10.1186/s12936-019-2786-y
|View full text |Cite|
|
Sign up to set email alerts
|

Evidence of asymptomatic submicroscopic malaria in low transmission areas in Belaga district, Kapit division, Sarawak, Malaysia

Abstract: Background Malaysia has declared its aim to eliminate malaria with a goal of achieving zero local transmission by the year 2020. However, targeting the human reservoir of infection, including those with asymptomatic infection is required to achieve malaria elimination. Diagnosing asymptomatic malaria is not as straightforward due to the obvious lack of clinical manifestations and often subpatent level of parasites. Accurate diagnosis of malaria is important for providing realistic estimates of mal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
60
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(63 citation statements)
references
References 45 publications
1
60
2
Order By: Relevance
“…Meta-analyses comparing prevalence rates determined by PCR versus LM have demonstrated that the proportion of submicroscopic P. falciparum infections in community samples substantially increases with declining malaria transmission intensity [14,15]. This trend was confirmed in the past few years by numerous molecular-epidemiological studies [15][16][17][18][19][20][21].…”
Section: Introductionmentioning
confidence: 87%
“…Meta-analyses comparing prevalence rates determined by PCR versus LM have demonstrated that the proportion of submicroscopic P. falciparum infections in community samples substantially increases with declining malaria transmission intensity [14,15]. This trend was confirmed in the past few years by numerous molecular-epidemiological studies [15][16][17][18][19][20][21].…”
Section: Introductionmentioning
confidence: 87%
“…In this review, 12 studies relied solely on microscopy for Plasmodium detection and species differentiation. The use of microscopy as the sole diagnostic method likely leads to an underestimation of the malaria burden in a speci c population (75), particularly in P. knowlesi and P. malariae infections that usually present at densities below the limit for microscopic detection (24). This review also provided insight in the disparity between microscopy and PCR in diagnosing malaria cases.…”
Section: Discussionmentioning
confidence: 99%
“…namely P. malariae or P. knowlesi. Furthermore, of the 28 studies, ten studies (12,24,25,28,31,34,41,52,61,63) conducted PCR in the whole samples regardless of the microscopy results in order to trace the sub-microscopic infections. In addition, 18 studies utilised only one method of detection for malaria.…”
Section: Description Of Included Studiesmentioning
confidence: 99%
“…Of those 18 studies tested for PCR, ten studies (7-9, 36-38, 41, 54, 56, 60) used all the microscopy positive cases, six studies (5,33,47,49,51,52) used more than 70% of the cases, one study (48) used 2.5% randomly selected cases, and one study (39) used 19% of microscopy positive cases for either P. malariae or P. knowlesi. Furthermore, of the 28 studies, ten studies (12,24,25,28,32,35,42,53,63,65) conducted PCR on all samples regardless of the microscopy results in order to trace the sub-microscopic infections. In addition, 18 studies utilised only one method of detection for malaria: 15 (34, 43, 44, 46, 50, 55, 57-59, 61, 62, 64, 66-68) by microscopy and three (27,40,45) by PCR.…”
Section: Description Of Included Studiesmentioning
confidence: 99%